2015 Charles F. Prentice Medal Award Lecture: Neural Organization of Binocular Vision. Issue 10 (October 2017) - Freeman, Ralph D.
Abstract : ABSTRACT: During a Research Career Development Award from the National Eye Institute, I spent a year at the University of Cambridge doing research with John Robson. The goal was to use a visual stimulation approach that had not been previously attempted, with the intention of exploring fundamental organization principles of the neural basis of binocular vision. The idea was to use sinusoidal gratings that drifted before both eyes such that the relative phase for one eye was fixed while that of the other was varied. This provided binocular stimuli of variable relative phase, i.e. retinal disparity, to enable testing of binocular response characteristics. We were able to obtain different types of disparity tuning functions for neurons in the primary visual cortex. This work, followed by extended investigations in Berkeley, provided basic information regarding response characteristics of simple and complex cells. We have also shown for monocular deprivation, an approximate model for human amblyopia, that many neurons remain connected to the deprived eye, as demonstrated with dichoptic activation. A selected portion of this work is described here.